Collins primary literacy: big book 1a - Hiatt, Kay; Stones, Brenda (Collins Educational London, 2008)
The "Collins Primary Literacy Big Book" is an engaging educational resource designed for early literacy development in young learners. It features a collection of carefully curated stories, poems, and activities that aim to enhance reading and writing skills. The book is structured to support phonics and vocabulary building, making it suitable for both classroom and home use. With large print and colorful illustrations, it captures children's attention and encourages interactive learning. This big book serves as a valuable tool for teachers and parents, fostering a love for reading while developing foundational literacy skills.